PENETAPAN TIMBAL, KADMIUM DAN TEMBAGA SECARA VOLTAMETRI PELARUTAN KEMBALI - Isa, Ishak (Jurnal Entropi, 2006)
The low consentration analysis of Lead, Cadmium, and Copper have been conducted by Differential Pulse Anodic Stripping Voltametry (DPASV) method using Hanging Mercury Dropiping Electrode (HMDE). DPASV method comprises two important steps. The firs step is deposition of a metal at the electrode sufase by electrolysis carry out by controlled potential. The second step is the metal stripping which have been precipitated at the electrode into the solution. The current, that is generated by stripping, is recorded by differential pulse mode. The optimum condition of instrumental parameters are deposition potential -700 mV, deposition lime 90 seconds, stripping rate 2000 rpm, 5 size of mercury drop and supporting electrolyte nitric acid at pH 1,5 which in produced by dilution of 50 L of 65% nitric acid suprapure until 10 mL solution. The precision (coefficient of variation) of analytical method was 9,24% Cd, 9,80% Pb, and 9,68% Cu. The accuracy of analytical method was 2,5% Cd, +1,76% Pb, and +7,30% Cu. The detection limit of analytical method was 29,9760 ng/L Cd, 42,4283 ng/L Pb, and 275,3222 ng/L Cu. The computation of concentration was based on twice addition standar technique.